TINGKAT KELULUSAN ALUMNI PENDIDIKAN KEPELATIHAN OLAHRAGA PADA SELEKSI CALON PEGAWAI NEGERI SIPIL NASIONAL TAHUN 2019 - Rivan Saghita Pratama; Sri Haryono; Wahadi Wahadi; Tri Tunggal Setiawan (UNIVERSITAS NEGERI MAKASSSAR, 2020)
The purpose of this study was to analyze the level of interest of alumni majoring in Sports Coaching Education (PKO) Faculty of Sports Science (FIK) Universitas Negeri Semarang (Unnes) participating in the 2019 National Civil Servant Candidate Admission Selection (CPNS) in Jawa Tengah. Type of research is descriptive research. This study found 93 alumni who took part in the 2019 CPNS selection. Alumni who did not pass the threshold to be opened were 41 alumni or 44.08%, Alumni who passed the threshold but did not enter the required rank again 15 people or 16.12% , Alumni who passed the SKB but were not included in the required rankings were 9 people or 9.67%, Alumni were declared to have passed to the final stage and were re-admitted 28 people or 30.10%. Conclusion of this study is that data from this research become the basis for PKO FIK Unnes department, continue to increase the percentage of alumni who pass the CPNS selection in the following year. The suggestion of this research is that the PKO FIK Unnes department must take a policy before taking the final project exam, students must pass the test threshold value similar to the CPNS selection test.